Photosensory adaptation mechanisms in hypocotyl phototropism: how plants recognize the direction of a light source. (11th January 2023) - Haga, Ken; Sakai, Tatsuya
Abstract: Plants recognize the direction of a light source and exhibit phototropic responses. Physiological studies have predicted that differences in the light intensity received by the cells on the irradiated and shaded sides of a coleoptile or hypocotyl cause differences in the amounts of photoproduct. This hypothetical photoproduct appears to regulate a signaling pathway that controls cell elongation in which cells under lower light intensity elongate more than those under higher light intensity. This results in a bending growth toward a light source and has been proposed as the photoproduct-gradient model of phototropism. In this review, we summarize recent findings on the photosensory adaptation mechanisms involving a blue-light photoreceptor, phototropin1 (phot1), ROOT PHOTOTROPISM2, NONPHOTOTROPIC HYPOCOTYL3 (NPH3), and another photoreceptor family, the phytochromes. The current evidence demonstrates that, in addition to the transition of the phot1–NPH3 photoreceptor complexes to their active state, the presence of a certain population of the phot1–NPH3 complexes showing a steady state, even in a light environment, is essential for recognition of the light source direction in phototropism. This is consistent with the photoproduct-gradient model, and a dissociation state of the phot1–NPH3 complex would be considered an entity of the hypothetical photoproduct in this model. Abstract : Recent findings on photosensory adaptation mechanisms in hypocotyl phototropism support the photoproduct-gradient model of phototropism and explain how plants recognize the direction of a light source.